2005
DOI: 10.1111/j.1464-410x.2005.05540.x
|View full text |Cite
|
Sign up to set email alerts
|

Gleason grading of prostate cancer in needle biopsies or radical prostatectomy specimens: contemporary approach, current clinical significance and sources of pathology discrepancies

Abstract: The Gleason grading system is a powerful tool to prognosticate and aid in the treatment of men with prostate cancer. The needle biopsy Gleason score correlates with virtually all other pathological variables, including tumour volume and margin status in radical prostatectomy specimens, serum prostate‐specific antigen levels and many molecular markers. The Gleason score assigned to the tumour at radical prostatectomy is the most powerful predictor of progression after radical prostatectomy. However, there are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 50 publications
1
98
1
5
Order By: Relevance
“…Indeed, tumors of higher Gleason grade appear to have increased cellular density (24), which will likely result in lower ADC values. Higher-grade tumors also have fewer ducts, and since Noworolski et al (34) suggested that combined DW-and DCE-MRI can distinguish between highly ductal and less ductal tissues within the prostate (34), one would expect this technique to improve tumor grading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, tumors of higher Gleason grade appear to have increased cellular density (24), which will likely result in lower ADC values. Higher-grade tumors also have fewer ducts, and since Noworolski et al (34) suggested that combined DW-and DCE-MRI can distinguish between highly ductal and less ductal tissues within the prostate (34), one would expect this technique to improve tumor grading.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of carcinoma in the tissue section, by surface area, was microscopically semiquantitatively scored as follows: 0 ϭ no carcinoma; 1 ϭ Ͻ10% carcinoma; 2 ϭ 10 -25% carcinoma; 3 ϭ 25-75% carcinoma; and 4 ϭ Ͼ75% carcinoma. In addition, tumors identified with both biopsies and radical prostatectomy were assigned a Gleason score (24).…”
Section: Patient Selection and Histologymentioning
confidence: 99%
“…Cancer grade is a key feature used to predict patient prognosis and in prescribing a treatment. Manual grading is time consuming and on account of its qualitative nature can lead to inter-and intra-observer variability [2], leading in turn to variable prognosis and suboptimal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…11 Inal and colleagues 12 reported a better histological quality sampling using a 16G needle to perform transrectal prostate biopsy and McCormack and colleagues 5 recently showed that the 16G needle does not increase prostate cancer detection. The goal of this study was to evaluate whether using a larger needle, 16G, to perform a prostate biopsy might increase the concordance between clinical and pathological GS.…”
Section: Discussionmentioning
confidence: 99%
“…Although undergrading biopsy GS is the most common problem, 11 overgrading biopsy GS may also occur; we did not evaluate this issue for 2 reasons. The first reason is that we did not consider biopsy GS less than 6 because it is generally considered the cutoff for low-dying risk from prostate cancer 15,16 and because Gleason pattern one and two are usually rare and seen in the transition zone, so it is unlikely to find a biopsy GS less than 6.…”
Section: Discussionmentioning
confidence: 99%